Roadmap to a Caring Economics: Beyond Capitalism and Socialism - Riane Eisler (Interdisciplinary Journal of Partnership Studies, 2017)
Our unprecedented technological, economic, and environmental challenges call for thinking that goes beyond capitalism and socialism, both of which were developed in early industrial times. This article outlines a caring economics or partnerism that supports not only human survival but also human development. It proposes a full-spectrum economic map and economic policies needed at this time when many jobs are being replaced by automation. It looks at issues generally ignored in the conversation about a new economics, such as intra-household resource allocation, the devaluation of women and the ‘feminine,’ and the view that caring for people, starting in early childhood, is merely reproductive rather than productive work. It examines economic systems in the larger context of societies orienting to either end of the domination-partnership social scale, showing the interaction between social values and economic priorities. It describes new metrics that, unlike GDP and GNP, demonstrate the economic value of caring for people and nature, and proposes other steps toward a caring economics as the basis for a more humane and sustainable future.